Neurological, visual, and MRI brain scan findings in 87 South African patients with HIV-associated cryptococcal meningoencephalitis. Issue 6 (June 2015) - Loyse, A.; Moodley, A.; Rich, P.; Molloy, S.F.; Bicanic, T.; Bishop, L.; Rae, W.I.D.; Bhigjee, A.I.; Loubser, N.D.; Michowicz, A.J.; Wilson, D.; Harrison, T.S.
Summary: Background: HIV-associated cryptococcal meningoencephalitis (CM) is a leading cause of adult meningitis in sub-Saharan Africa. Neuroradiological data is however limited to case reports and small case series from developed countries and/or immunocompetent patients. Methods: Eighty seven patients aged ≥18 hospitalized with a first episode of CM had magnetic resonance (MRI) imaging during the first two weeks of admission. A subset of eleven patients had follow-up scans approximately one month from their initial MRI scan. All had prospectively-recorded detailed neurological and visual examinations. Results: An abnormal finding on neurological examination was detected in 33 (39%) patients. 38 (48%) patients experienced some visual loss. Neuroradiological lesions presumed to be cryptococcosis-related, as defined by the presence of dilated Virchow Robin spaces, pseudocysts or cryptococcomas, enhancing nodules, hydrocephalus, meningitis, focal perilesional oedema and infarcts, were detected in 55 (63%) patients. MRI findings suggestive of a second diagnosis were found in 18 (21%) patients. Visual loss was associated with the presence of cryptococcal-related lesions ( p  = 0.02). Blindness was associated with raised intracranial pressure (ICP) ( p  = 0.02). Of eleven patients with paired scans, brain swelling was identified on the initial scan in only one patient. Conclusion: The majority of patients had MRI brain scan abnormalities presumed secondary to CM. Dilated Virchow Robin spaces were the commonest neuroradiological lesion. Visual loss was associated with the degree of cerebral involvement as reflected by the presence of MRI abnormalities. Blindness was associated with the presence of raised ICP. Initial generalised brain swelling does not appear to be common, but further studies with paired scans are needed.